1995
DOI: 10.1109/20.364619
|View full text |Cite
|
Sign up to set email alerts
|

A solution for the three dimensional rail gun current distribution and electromagnetic fields of a rail launcher

Abstract: A bstruct-Rail guns generate electromagnetic signatures that contain frequencies extending from quasi-dc to tens of kHz.The c h a r a c t e r i z a t i o n of these fields for electromagnetic compatability concerns remains, however, largely unexplored. Accordingly, this paper includes a discussion of the theoretical models used to predict the inductance gradient, the transient behavior of the currents produced in the rail gun structure, the dynamical generation of the external fields, and a comparison of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…3, where the peak amplitude is 160 U. This equation applied to the parallel plate rails gives L = 0.52 pH [6]. The railgun inductance gradient, L', is taken as, L divided by I, or 0.52 pWm.…”
Section: Resultsmentioning
confidence: 99%
“…3, where the peak amplitude is 160 U. This equation applied to the parallel plate rails gives L = 0.52 pH [6]. The railgun inductance gradient, L', is taken as, L divided by I, or 0.52 pWm.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the solenoidal nature of magnetic fields, the lines of force must wrap around the current sheet, resulting in a field with reversed direction in front of the current sheet. By solving the full boundary value problem with the conductors configured as illustrated, it can be shown that the magnetic field in front of (upstream side) the current sheet is much smaller than inside (downstream side) the current loop [29]. Nevertheless, there will be a region of finite width inside the current sheet where the magnetic field is reversed; this is interesting because it implies that the plasma near the leading edge of the current sheet will be accelerated opposite to the sheet velocity vector, v. The magnetic field reverses at some point inside the current sheeteventually reaching its peak value at the back edge of the current sheet.…”
Section: Final Report For Afosr : Current Sheet Phys and Dynmentioning
confidence: 99%
“…Using a conformal mapping technique to determine the electromagnetic fields in a parallel rail launcher, ref. [73] provides the necessary tabular data to determine the actual value of the inductance-per-unit-length for a given electrode aspect ratio. The graph in Fig.…”
Section: Inductance-per-unit-lengthmentioning
confidence: 99%